Impact of the COVID-19 pandemic on youth delinquency: A discontinuous growth analysis - Li, Nan; Quintana, Diana; Shelton, Matthew; Grigorenko, Elena L. (Frontiers in Education, 2023)
This study aimed to investigate (a) the immediate and long-term changes in youth offending counts among 138 neighborhoods within a large metropolitan area in the context of COVID-19 and (b) the extent to which the socioeconomic composition of the neighborhoods accounted for variations of the changes. Discontinuous growth models were applied to demonstrate the changes in offenses against a person, property offenses, and drug-related offenses one-year prior to, at (March 2020), and one-year following the pandemic. At the onset of the pandemic, we registered an immediate reduction in offenses against a person and property offenses but not in drug-related offenses. There was a steeper declining trend for property offenses one-year following the pandemic as compared with that one-year prior to the pandemic. The neighborhood concentration of affluence and poverty was not related to the immediate reduction in any type of delinquency. We conclude that the COVID-19 pandemic not only had an abrupt but also an enduring impact on youth delinquency.